Rencana Sarana Pengolahan Limbah B3 Covid-19 di Kota Ambon - Adnan Affan Akbar Botanri; Rinaldy Makatita; Vivi Sopacua (TATALOKA, 2021)
Corona Virus or Covid-19 has taken over all the world, including Indonesia. This virus outbreak has become a pandemic because of its lightning-fast spread and greater number of death rate. Ambon as one of the cities in Eastern Indonesia is also affected by Corona Virus.The higher the positive cases in Ambon, the higher the hazardous and toxic waste production (B3). Now, the government of Maluku province is preparing B3 waste management facilities, so that this research aims to investigate the appropriate location for this waste management. This research was a qualitative descriptive by applying a SIG method, that was analysing the area function with the parameter of slope, soil type, and rainfall. The area function could be used to consider the development plans of an area. Then, the data of buildings was used as a basic to determine the ideal area with the service range of 500 meter in accordance with the standard distance of B3 waste management facilities from surrounding buildings. The research findings show four alternative areas of B3 waste management facilities in Ambon. These four areas are safe to be built hazardous and toxic waste (B3) management facilities since these are located far away from the settlements.